Luciferase complementation based-detection of G-protein-coupled receptor activity - Hideaki Yano; Ning Sheng Cai; Jonathan A Javitch; Sergi Ferré (BioTechniques)
Protein complementation assays (PCA) are used as pharmacological tools, enabling a wide array of applications, ranging from studies of protein–protein interactions to second messenger effects. Methods to detect activities of G protein-coupled receptors (GPCRs) have particular relevance for drug screening. Recent development of an engineered luciferase NanoLuc created the possibility of generating a novel PCA, which in turn could open a new avenue for developing drug screening assays. Here we identified a novel split position for NanoLuc and demonstrated its use in a series of fusion constructs to detect the activity of GPCRs. The split construct can be applied to a variety of pharmacological screening systems.